(untitled) - Dravecka, Lenka (Doprava a spoje, 2005)
The natural place for synchronization is in an area where the traffic demand is too high for the actual capacity. When we envision the future, crowded areas might become normal. This study is framed within a PhD research that investigates the acceptability of controllers in the collaborative context, and in particular for the task of monitoring aircraft's speed adjustment and assigning flight level to achieve synchronized flows. This paper presents one first step towards the evaluation of operational feasibility of this concept in Central European Upper Airspace: the improvement of controllers' productivity through adequate task sharing in the traffic synchronization activity and proposes a simple synchronization model.